Groundnuts in a nutshell - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Recommendations for Improved Groundnut Production in Zambia By B M Siamasonta, K Kanenga, J C Musanya & P M Hamazakaza, Ministry of Agriculture, Food and Fisheries, Zambia & SADC/ICRISAT Groundnut Project, 2000. 20 pp.